2012
DOI: 10.1530/erc-11-0389
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen and androgen receptors in differentiated thyroid cancer: an additional criterion to assess the patient's risk

Abstract: Estrogen receptor (ER) and androgen receptor (AR) may be expressed in thyroid tumors, but their prognostic role is controversial. We investigated whether ER and AR expressions could confer a more aggressive phenotype to thyroid tumors. We enrolled 91 patients (13 males and 78 females, mean age 49.3±14.8 years) bearing small (T1 in the 2006 TNM system) differentiated thyroid cancers (DTC). Thirty-eight tumors were incidental histological findings. Using immunohistochemistry, we evaluated ERα, ERβ, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 38 publications
4
61
2
2
Order By: Relevance
“…Moreover, the transition from FTAs to FTCs seemed to go along with the loss of ESR2 expression (Heikkila et al 2013). This fits well with the lack of ERb expression in papillary carcinomas and the finding of ERb negativity in some small differentiated thyroid carcinomas with a more aggressive phenotype (Di Vito et al 2011, Magri et al 2012. Lower expression of ERb was also described in undifferentiated thyroid stem and progenitor cells when compared with differentiated human thyrocytes ).…”
Section: Er Expression and Outcome Of Thyroid Cancersupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, the transition from FTAs to FTCs seemed to go along with the loss of ESR2 expression (Heikkila et al 2013). This fits well with the lack of ERb expression in papillary carcinomas and the finding of ERb negativity in some small differentiated thyroid carcinomas with a more aggressive phenotype (Di Vito et al 2011, Magri et al 2012. Lower expression of ERb was also described in undifferentiated thyroid stem and progenitor cells when compared with differentiated human thyrocytes ).…”
Section: Er Expression and Outcome Of Thyroid Cancersupporting
confidence: 77%
“…This assumption is also supported by the findings that ERa positivity was associated with a more aggressive phenotype of differentiated thyroid cancer and of an eight to ten times higher expression of ERa in undifferentiated, growth-prone thyroid stem and progenitor cells than in differentiated thyrocytes (Magri et al 2012.…”
Section: Er Expression and Outcome Of Thyroid Cancermentioning
confidence: 54%
“…6), can be explained by the finding that cell growth is primarily regulated via ERa, whereas ERb is involved in the control of apoptosis and suppressive functions (Chen et al 2008). In taking this view, two recent reports that correlated ERa positivity and loss of ERb expression in differentiated thyroid carcinomas with a more aggressive phenotype and a poor outcome are of interest (Heikkila et al 2012, Magri et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…With special reference to hormone receptor expression in thyroid tumors, a recent study (8) on the immunohistochemical expression of ER and androgen receptor (AR) in DTC showed that ERa was acquired or increased in tumor samples as compared with the corresponding normal tissue, whereas AR and ERb expression was decreased in tumors compared with the surrounding normal tissue. These patterns appeared also to be associated with the clinical behavior, being the high expression of ERa and AR and the low expression of Erb associated with a more aggressive phenotype.…”
Section: Introductionmentioning
confidence: 99%